Pharaohs on both sides of the blood-red waters : prophetic critique of empire ; resistance, justice, and the power of the hopeful sizwe -- a transatlantic conversation - Boesak, Allan, 1945- (Eugene, Oregon : Cascade Books, 2017)
After the civil rights and anti-apartheid struggles, are we truly living in post-racial, post-apartheid societies where the word struggle is now out of place? Do we now truly realize that, as President Obama said, the situation for the Palestinian people is "intolerable"? This book argues that this is not so, and asks, "What has Soweto to do with Ferguson, New York with Cape Town, Baltimore with Ramallah?" With South Africa, the United States, and Palestine as the most immediate points of reference, it seeks to explore the global wave of renewed struggles and nonviolent revolutions led largely by young people and the challenges these pose to prophetic theology and the church. It invites the reader to engage in a trans-Atlantic conversation on freedom, justice, peace, and dignity. These struggles for justice reflect the proposal the book discusses: there are pharaohs on both sides of the blood-red waters. Central to this conversation are the issues of faith and struggles for justice; the call for reconciliation--its possibilities and risks; the challenges of and from youth leadership; prophetic resistance; and the resilient, audacious hope without which no struggle has a future. The book argues that these revolutions will only succeed if they are claimed, embraced, and driven by the people.
Introduction : seeing Satan fall like lightning from heaven : the new militancy and the hopeful sizwe -- Pharaohs on both sides of the blood-red waters : why we cry, how we cry, and how can cry -- Interrupting the globalization of indifference : empire, faithful resistance, and prophetic pathos -- The divine favor of the unworthy : when the fatherless son meets the black messiah -- When ubuntu takes flight : justice, politics, reconciliation, and spirit of ubuntu -- "The righteousness of our strength" : reconciliation and the historic obligation of the oppressed -- Deification, demonization, and dispossession : Mandela, prime evil, and the hope that will not go away -- "A hope unprepared to accept things as they are" : prophetic theology--speaking truth from the edge.
Includes bibliographical references (pages 227-234) and index.
Keywords: Social justice -- Religious aspects; Human rights -- Religious aspects; Human rights -- Religious aspects; Social justice -- Religious aspects